Ascertaining the semantic and linguistic level of perceived risk in e-business interactions - Hussain, Omar; Chang, Elizabeth; Dillon, Tharam S.; Hussain, Farookh Khadeer (Institute of Electrical and Electronics Engineers (IEEE) Computer Society, 2008)
By analyzing the level of perceived risk in the domain of e-business, the interaction initiating agent can determine beforehand whether or not it will achieve its desired outcomes and the associated consequences to it in interacting with the other agent. In our previous work, we have proposed a methodology by which the initiating agent ascertains the numeric level of perceived risk in forming an interaction. In this paper, we propose a methodology by which the initiating agent of the interaction determines the semantic level of perceived risk, for it to be utilized while making an informed interaction-based decision with an agent.